2021
DOI: 10.1002/jha2.153
|View full text |Cite
|
Sign up to set email alerts
|

High serum ferritin alone as a predictor of mortality and hemophagocytic lymphohistiocytosis

Abstract: We report here utility of high serum ferritin alone as a predictor of mortality and diagnosis of hemophagocytic lymphohistiocytosis (HLH). We compared mortality in patients with high serum ferritin >5000 ng/mL versus <5000 ng/mL and looked for presence of HLH. Mortality was significantly higher (P‐value .0048) in patients with serum ferritin levels >5000 ug/dL. Of 21 patients with high serum ferritin, a median of three criteria were fulfilled to diagnose HLH. All patients had features of immune‐activation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Lin et al [21] presented the usefulness of regular ferritin measurements in predicting treatment outcomes in patients with HLH. Additionally, Kohli et al [22] showed that high serum ferritin levels are highly predictive of mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [21] presented the usefulness of regular ferritin measurements in predicting treatment outcomes in patients with HLH. Additionally, Kohli et al [22] showed that high serum ferritin levels are highly predictive of mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%